Creatine Supplementation
The sporting field of today is ultra-competitive. The professionalisation and influx of money to many sports has drawn athletes from across the globe. Using all potential avenues - physical, psychological, nutritional, etc. - for improved performance has become vital to be competitive on the world stage. Nutritional supplements have become popular with athletes. Creatine monohydrate is one such supplement that has become widespread in recent years due to its availability, relatively low cost and legality. Many track athletes - including Linford Christie - have used creatine monohydrate (Cr.H2O) for its claimed benefits. This is despite the fact that the benefits of creatine supplementation have yet to be conclusively proven in laboratory tests. Studies involving swimmers, rowers, sprinters, rugby league players and cyclists have given results both for and against creatine supplementation. The aim of this paper is to critically analyse the current literature, outline the possible benefits / side effects of creatine supplementation and to provide the athlete with recommendations.